THE EFFECT OF ORGANIC MEDIA ON THE QUALITY OF Santalum album SEEDLING - Asri Insiana Putri (Jurnal Pemuliaan Tanaman Hutan, 2008)
The quality of Santalum album seedling is influenced by growing media where their root grow and develop. This research was conducted to confirm that organic growing media is a good characteristics as top soil media and to determine the quality index value as indicator of seedling quality. There types of media; top soil, composted sawdust and pure sawdust were arranged in a completely randomized design with 4 replicates of 5 seeds. The observation periode was 8 month, from January until September 2007. The resuly showed that index value for S, album seedling in organic media is as relatively high as in top soil media; 1,42 for top soil, 1,10 for composted sawdust and 1,08 for pure sawdust.